Remarks at the World Government Summit - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, remarked that for more than 60 years, the World Bank Group has been working with governments in developing counties to reduce poverty and promote human dignity. Good governance is the foundation for all development. Delivering quality public services and creating conditions that encourage businesses to create jobs are fundamental to building opportunity and prosperity for all. The global landscape suggests that reaching these objectives won’t be easy. Economic growth, the most powerful poverty reduction force the world has ever known, is slowing globally. Many emerging markets are suffering sharp reductions in growth because of declining demand from China and lower commodity prices. Warmer temperatures potentially linked to climate change made 2015 the hottest year in history; and the most powerful El Niño on record is affecting the lives and livelihoods of billions across the globe. Many parts of the world are becoming more fragile, making quality leadership and good governance ever more important.